A Framework for the Assessment of Temporal Artifacts in Medium Frame-Rate Binary Video Halftones. (17th August 2010) - Rehman, Hamood-Ur; Evans, Brian L.
Abstract : Display of a video having a higher number of bits per pixel than that available on the display device requires quantization prior to display. Video halftoning performs this quantization so as to reduce visibility of certain artifacts. In many cases, visibility of one set of artifacts is decreased at the expense of increasing the visibility of another set. In this paper, we focus on two key temporal artifacts, flicker and dirty-window-effect, in binary video halftones. We quantify the visibility of these two artifacts when the video halftone is displayed at medium frame rates (15 to 30 frames per second). We propose new video halftoning methods to reduce visibility of these artifacts. The proposed contributions are (1) an enhanced measure of perceived flicker, (2) a new measure of perceived dirty-window-effect, (3) a new video halftoning method to reduce flicker, and (4) a new video halftoning method to reduce dirty-window-effect.